Recurrence of common bile duct stones after choledocholithotomy in elderly patients: risk factor analysis and clinical prediction model development - Wang, Han; He, Yu-qi; Dong, Shi-yang; Zhong, Wan; Tao, Ping; Yang, Shi-yong; Liu, Zi-jun (Frontiers in Medicine, 2023)
The reasons for the recurrence of common bile duct stones (CBDS) in elderly patients after choledocholithotomy are still unclear. This study aims to establish a prediction model for CBDS recurrence by identifying risk factors.We conducted a retrospective analysis of 1804 elderly patients aged 65 years and above who were diagnosed to have CBDS and were admitted to Nanjing First Hospital between January 1, 2010, and January 1, 2021. According to inclusion and exclusion criteria, 706 patients were selected for the final analysis. The patients were assigned to two groups according to the presence or absence of CBDS recurrence, and their clinical data were then statistically analyzed. Subsequently, a prediction model and nomogram were developed, evaluating effectiveness using the concordance index (C-index).Of the 706 elderly patients, 62 patients experienced CBDS recurrence after surgery, resulting in a recurrence rate of 8.8%. The multivariate Cox analysis showed that prior history of cholecystectomy (hazard ratio [HR] = 1.931, 95% confidence interval [CI]: 1.051-3.547, P = 0.034), white blood cell (WBC) count ≥ 11.0 × 10 9 /L (HR = 2.923, 95% CI: 1.723-4.957, P < 0.001), preoperative total bilirubin (TBIL) level ≥ 36.5 mmol/L (HR = 2.172, 95% CI: 1.296-3.639, P = 0.003), number of stones ≥ 2 (HR = 2.093, 95% CI: 1.592-5.294, P = 0.001), maximum stone diameter ≥ 0.85 cm (HR = 1.940, 95% CI: 1.090-3.452, P = 0.024), and T-tube drainage (HR = 2.718, 95% CI: 1.230-6.010, P = 0.013) were independent risk factors of CBDS recurrence in elderly patients after choledocholithotomy. A postoperative CBDS recurrence prediction model was constructed with a C-index value of 0.758 (95% CI: 0.698-0.818) and internal validation value of 0.758 (95% CI: 0.641-0.875).A history of cholecystectomy, WBC count ≥ 11.0 × 10 9 /L, preoperative TBIL level ≥ 36.5 mmol/L, number of stones ≥ 2, maximum stone diameter ≥ 0.85 cm, and T-tube drainage are the independent risk factors of CBDS recurrence after choledocholithotomy in elderly patients. Our developed prediction model for CBDS recurrence has good predictive ability and can help predict the prognosis of patients with CBDS.